PRE-CLINICAL STUDY OF MIKOVITAM INFLUENCE ON LABORATORY RATS - Лясота, В. П.; Сідніченко, І. В. (Scientific Progress & Innovations, 2013)
In the article the data of Mikovitam influence on the metabolism of white rats are stated. It is established that application of Mikovitam in a dose of 0,9 g promotes increase in haemoglobin at 2,7 %, erythrocytes at 4,4 %, the total protein – 2,4 %, and also increases the weight of white rats on 10,4 % compared with animals of a control group. The differences in glucose, the total lipids and cholesterol concentration and aminotransferase activity were not established. It is offered to study bioactive compound, as a supplement to feed compound of a livestock for activation of natural resistance level, metabolic processes and growth intensity.